Gene co-expression regulatory network analysis identifies novel regulators in light signaling pathways in Arabidopsis - Bai, Yanan; Pham, Vinh Ngoc; Huq, Enamul (Frontiers in Photobiology, 2025)
Plants have evolved with complex sensory systems to recognize signals from multiple environmental conditions. A light signal is one of the most important environmental factors that regulates not only photomorphogenesis but also the developmental strategy of plants throughout their life cycle. The molecular mechanisms of the light signaling modules and the interactions between light and other environmental signals have been studied extensively. However, to enhance plant growth, particularly in crop production, we need to gain a deeper understanding of how light regulates plant development within gene regulatory networks (GRNs). Understanding GRNs is important to identify not only the novel genes and transcription factors in light signaling pathways but also the factors that connect light signaling and other environmental signals. Weighted gene co-expression network analysis (WGCNA) has been used to study GRN. We applied WGCNA to 58 RNA-seq samples of wild-type Arabidopsis grown under different light treatments and built the gene co-expression networks. We identified 14 different modules that are significantly associated with different light treatments. Among them, the honeydew1 and ivory display significant association with the dark-grown seedlings. Many hub genes identified from these modules are significantly enriched in light responses, including responses to red, far-red, blue light, light stimulus, auxin responses, and photosynthesis. Although we found many known transcription factors in these modules, we also identified several unknown genes and transcription factors that are significantly associated with the honeydew1 module and highly differentially expressed between dark and light conditions. To examine whether the hub genes in the honeydew1 module play a role in light signaling, we isolated mutants in selected hub genes and measured hypocotyl lengths under dark, red, and far-red light conditions. These assays showed that four hub genes are involved in regulating light signaling pathways. This study provides a new approach to identifying novel genes in GRNs underlying light responses in Arabidopsis.